Connotative Meaning in Selected Superman Is Dead Song Lyrics - I Kadek Dio Triana; Ni Made Suwari Antari (CV. Ulil Albab Corp, 2023)
The purpose of this analysis is to find out some words that contains with connotative meaning as well as the conveyed message from the song writer on specific object of research in the four superman is dead’s songs based on Jackson (2014) and Hook (1975) theories. The data was taken from the lyrics that was downloaded from the band official site, three of the songs that was analyzed are: “Memories of rose”, “Blackmarket love”, “Goodbye whiskey”, and